Implementation of Good Governance to Improve Public Services at the Ciamis Regency Population Service from a Public Service Perspective - Arie Nurazizah; Fauzan Ali Rasyid; Lutfi Fahrul Rizal (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the implementation of Good Governance principles in improving public services at the Department of Population and Civil Registration (Disdukcapil) of Ciamis Regency from the perspective of Siyasah Dusturiyah. The purpose of this research is to analyze how principles such as transparency, accountability, participation, professionalism, and efficiency are applied in civil administrative services and how Islamic values in governance strengthen these efforts. A qualitative descriptive approach was used with juridical-empirical and normative methods, supported by primary data through field observation and interviews. The findings show that while Disdukcapil Ciamis has initiated service innovations such as the SILANCAR system and the “Jempol Si Manis” outreach program, challenges remain due to limited human resources, infrastructure, and shortages of e-ID card blanks. In the Siyasah Dusturiyah framework, public service is considered a trust (amanah) that must be carried out fairly, transparently, and responsibly. Therefore, institutional capacity building, digital technology adoption, and internalizing Islamic values are strategic steps to achieve good and competitive governance.